2014
DOI: 10.1016/j.epsl.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic intensity variations for the past 8 kyr: New archaeointensity results from Eastern China

Abstract: In this study, we have carried out paleointensity experiments on 918 specimens spanning the last ∼7 kyr, including pottery fragments, baked clay and slag, collected from Shandong, Liaoning, Zhejiang and Hebei Provinces in China. Approximately half of the specimens yielded results that passed strict data selection criteria and give high-fidelity paleointensities. The virtual axial dipole moments (VADMs) of our sites range from ∼2 × 10 22 to ∼13 × 10 22 Am 2 . At ∼2250 BCE our results suggest a paleointensity lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 71 publications
7
40
0
Order By: Relevance
“…These high values are in agreement with recently published data by Shaar et al (4) and represent one of the Levantine Iron Age "geomagnetic spikes." These anomalies, first reported by Ben-Yosef et al (2), were defined by Cai et al (32) as "a sharp increase in the field intensity to more than twice the present value (∼160 ZAm 2 VADM) in less than 500 years." Following this definition and the current data available for the Levant (4), there is evidence for at least two such spikes, one during the 10th century BCE [cf.…”
Section: Discussionmentioning
confidence: 93%
“…These high values are in agreement with recently published data by Shaar et al (4) and represent one of the Levantine Iron Age "geomagnetic spikes." These anomalies, first reported by Ben-Yosef et al (2), were defined by Cai et al (32) as "a sharp increase in the field intensity to more than twice the present value (∼160 ZAm 2 VADM) in less than 500 years." Following this definition and the current data available for the Levant (4), there is evidence for at least two such spikes, one during the 10th century BCE [cf.…”
Section: Discussionmentioning
confidence: 93%
“…Necessity of the cooling rate correction has also been emphasized in many studies because the difference in that rate could result in biased archeointensity estimates (e.g., Mitra et al 2013;Cai et al 2014). For example, Usui (2013) reported that the cooling rate effect resulted in a 37% to 46% overestimated paleointensity for an oceanic gabbro, although it is not the case of the archeointensities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, brand new data with modern paleointensity techniques have been published from East Asia outside Japan, for example, Korea (Yu et al 2010;Hong et al 2013) and China (Cai et al 2014). In 1960s to 1970s, a group of Japanese researchers had made systematic oriented-sample collections from baked clay at many pottery kilns excavated in and around Sakai city, Osaka prefecture, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Here we used the GEOMAGIA50.v3 database (Donadini et al 2006;Korhonen et al 2008;Brown et al 2015) to which we added recent archeo-and paleointensity results (Cai et al 2014(Cai et al , 2015Cromwell et al 2015;de Groot et al 2015;Di Chiara et al 2014;Gallet et al 2008Gallet et al , 2009Gallet & Al Maqdissi 2010;Hong et al 2013;Kapper et al 2015;Kissel et al 2015;Osete et al 2015;Shaar et al 2015;Stillinger et al 2015). Concerning the data compiled in this version of GEOMAGIA, the Mesopotamian data from Nachasova & Burakov (1995 were modified according to .…”
Section: Appendix A: Gmag9k Axial Dipole Evolutionmentioning
confidence: 99%